Analisis Perlindungan Konsumen Dalam Kontrak Elektronik Pada Transaksi E-Commerce Indonesia - Hapsari, Crescentia Viola Priscilla Audra; Lie, Gunardi (Media Hukum Indonesia (MHI), 2025)
The swift growth of online shopping in Indonesia has given rise to electronic contracts (e-contracts) as the primary instrument for online transactions. However, this dynamic also presents legal challenges, particularly regarding the protection of consumers, who often find themselves in a weak bargaining position. The purpose of the research is to examine consumer protection in e-contracts based on the Indonesian regulatory framework, identify weaknesses in implementation, and offer academic and practical recommendations.The analysis found that consumers frequently face various obstacles, including complex and difficult-to-understand contract clauses, limited access to online dispute resolution mechanisms, and insufficient transparency of information related to rights and obligations within electronic contracts. Furthermore, there is a significant gap between existing legal regulations and their actual implementation. Therefore, this study recommends strengthening regulations concerning standard clauses in electronic contracts, developing and optimizing online dispute resolution mechanisms, improving consumers’ legal and digital literacy, and enchancing coordination among supervisory and law enforcement agencies to establish a fairer and more transparent e-commerce governance. The results are anticipated to help the improvement of electronic contract governance within Indonesia’s e-commerce transaction ecosystem.